Serum Cystatin C Predicts AKI and the Prognosis of Patients in Coronary Care Unit: a Prospective, Observational Study - Yugang Hu; Huilan Liu; Liguo Du; Jing Wan; Xiaoning Li (Karger Publishers, 2017)
Background/Aims: Acute Kidney Injury (AKI) is a serious clinical state associated with high morbidity and mortality, particularly in critical ill patients. We investigated the hypothesis that serum Cystatin C (sCysC) is a good predictor for AKI and may affect the short-term prognosis of coronary care unit (CCU) patients. Methods: In this prospective, observational study, we screened 412 adults admitted to the CCU from January 1, 2014 to June 1, 2015 at Zhongnan Hospital of Wuhan University. Serum samples were obtained at the time of admission, and sCysC was quantified through nephelometry. AKI was defined based on KDIGO-AKI criteria. After the patients' hospital discharge, the survivors in this study were followed up for up to 2 years. The primary endpoint was the incidence of AKI stratified by severity stage, while the second endpoints included 2-year mortality, rehospitalization and failure in renal recovery rates, as well as the progression of AKI to CKD. Results: According to the KDIGO-AKI criteria, AKI occurred in 130 (31.6%) patients. After multivariate adjustments, the highest quartile of sCysC was associated with a 9-fold increased risk of incident AKI compared with the lowest quartile. For predicting AKI, sCysC [area under the receiver operating characteristic curve (AUC=0.842)] outperformed β2-micro globulin (AUC=0.813) and the clinical model (AUC=0.777), and a cutoff of 1.255 mg/L yielded good sensitivity and specificity. After a median 19.8-month follow-up, 112 (27.2%) patients died within 2 years after admission. The sCysC independently predicted the risk of 2-year mortality [adjusted odds ratio (OR), 4.955; 95% confidence interval (95% CI), 2.853 to 8.603] and rehospitalization (OR, 3.128; 95% CI, 2.011 to 4.867), as well as renal recovery failure (OR, 3.618, 95% CI, 1.753 to 7.463). Conclusions: Serum CysC is a strong predictor of AKI and the short-term prognosis of CCU patients.